Isbat Marriage Resolution in Indonesia: A Maslahah Approach: Resolusi Isbat Nikah di Indonesia: Sebuah Pendekatan Maslahah - Sudirman, Sudirman; Iskandar, Iskandar (Institut Agama Islam Negeri (IAIN) Pontianak, 2020)
The problems related to Isbat of marriages (isbat nikah) are still arising because marriage without registration is still being done. The weak of regulation and suboptimal efforts to regulate marriages that were not registered after 1974 added to the Isbat of a marriage behavior problem. The focus of this research is Isbat of marriage in a review maslahah. This research uses qualitative descriptive methods. The results showed that Isbat of marriage is examined in terms of maslahah will place it in terms of maslahah hajjiyyah. This is supported in terms of the level of benefit. A marriage will not be able to find perfect happiness if the fulfillment of the Hajjiyah in the marriage is not fulfilled. Moreover, the Isbat of marriage is a way to fulfill administrative requirements in re-registering marriages that have been made. In addition to the position of the issue, there must also be more concrete regulations that regulate certain matters related to marriage issues so that administrative order in marriage is created.